Effects of intercropping with post-grafting generation of Impatiens balsamina on potassium uptake of grape seedlings under cadmium stress. Issue 5 (May 2019) - Yang, Liu; Wang, Ting; Xia, Dan; Lin, Lijin; Liao, Ming'an
Abstract: Grape seedlings and post-grafting generation of Impatiens balsamina were used as materials to intercrop for exploring the effects of the potassium uptake of grape seedling under the stress of cadmium. There were five treatments in this experiment including one grape seedling monoculture and four intercropping treatments. According to the results, the testing indicated that the content of total potassium in leaf, stem and root of seedling and soil available potassium in grape seedling monoculture were all higher than that in intercropping treatments, and the content was all ranked as: grape seedling intercropping with PSSG < intercropping with PSDG < intercropping with PSG < intercropping with UG < grape seedling monoculture. In terms of soil available potassium, the content had no significant difference when grape seedling intercropped with PSSG, PSDG and PSG. So while intercropping with Impatiens balsamina of post-grafting generation, the total potassium and soil available content could not increase. On the contrary, it decreased. Therefore, intercropping treatment did not play a positive role in potassium uptake and had no significant promoting effects on plant growth and development.